2022
DOI: 10.3389/fendo.2022.918733
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Stress Impairs Pericyte Response to Optogenetic Stimulation in Pancreatic Islets

Abstract: Pancreatic islets are highly vascularized micro-organs ensuring whole body glucose homeostasis. Islet vascular cells play an integral part in sustaining adequate insulin release by beta cells. In particular, recent studies have demonstrated that islet pericytes regulate local blood flow velocity and are required for maintenance of beta cell maturity and function. In addition, increased metabolic demand accompanying obesity alters islet pericyte morphology. Here, we sought to explore the effects of metabolic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…In mice, pericytes provide direct trophic support for beta cells, contributing to their proliferation, maturation and insulin secretion (18)(19)(20)(21), or indirectly by participating in ECM synthesis (22). Pericytes may also impact beta cell health and function by maintaining proper blood supply to endocrine cells as they are important regulators of islet capillary diameter and blood flow (17,23,24). Importantly, pericyte-mediated changes in islet blood flow are required for proper islet hormone secretion and glucose homeostasis in mice (25) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mice, pericytes provide direct trophic support for beta cells, contributing to their proliferation, maturation and insulin secretion (18)(19)(20)(21), or indirectly by participating in ECM synthesis (22). Pericytes may also impact beta cell health and function by maintaining proper blood supply to endocrine cells as they are important regulators of islet capillary diameter and blood flow (17,23,24). Importantly, pericyte-mediated changes in islet blood flow are required for proper islet hormone secretion and glucose homeostasis in mice (25) .…”
Section: Introductionmentioning
confidence: 99%
“…Changes in islet pericyte density, morphology and function occur under pathophysiological conditions. In mouse models of type 2 diabetes, for instance, islet pericytes enlarge and adopt a myofibroblast-like appearance (15, 26, 27), which interferes with their capacity to regulate islet blood flow (24). Although pericytes have important physiological and pathophysiological functions in islets, it is not known what happens to this cell population during T1D development.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, α-SMA labels contractile pericytes on capillaries ( 12 , 27 , 28 ). Second, NG2 is expressed in morphologically distinct arteriolar smooth muscle cells, also expressing α-SMA ( 14 , 35 ). Finally, NG2 is expressed in oligodendrocyte precursor cells (OPCs), also called NG2-glia ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that pericytes are electrically responsive, enabling optogenetic control of their activity ( 14 , 27 , 28 , 35 ). In accordance with a role for pericytes in blood flow regulation described previously in the cerebellum ( 13 ) and the cortex ( 12 ), manipulation of NG2-positive cell activity through optogenetic stimulation in vivo was able to modify blood flow in the ME.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation